Introduction - Alessandro Roncaglia (PSL Quarterly Review, 2010)
This is the first “regular” issue of PSL Quarterly Review, after the two special issues for 2008 and 2009. As an economists’ phoenix, the Review is born out of the ashes of its forerunner, the BNL Quarterly Review, after a change in ownership, from Banca Nazionale del Lavoro to the Associazione Paolo Sylos Labini. The “new” Quarterly retains the editor and the editorial board of the “old” Quarterly, and its orientation towards scientific research and debate in the field of economic theory and policy, with specific but not exclusive attention to monetary and financial issues and with no preconceived choice of field among the different schools of thought. In essence, we have a new series of an old journal.